Analyses of Chemical and Physical Egg Quality Parameters of Laying Hens Housed in Different Conditions in Turkey - Reyhan Selin Uysal Afacan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The aim of the present study is to determine the content of chemical and physical quality parameters of hen eggs (liquid whole egg (LWE), liquid egg yolk (LEY), and liquid egg white (LEW)) produced for different housing and feeding conditions in Turkey. Chemical quality parameters (protein, lipid, and moisture) and physical quality parameters (total soluble solid (°Brix), pH, conductivity, and yolk:white ratio) were analyzed using different egg samples. Kjeldahl, wet ashing, and oven-drying official methods were used for the protein, total lipid, and moisture analyses of egg samples. The highest protein content in the LEY and LEW samples were found to be 19.0% and 15.13%, respectively for the tenth sample having fortified feeding (selenium+DHA) parameters. For LWE samples, it was also obtained 15.65% with the second sample having a not fortified feeding parameter. The highest total lipid content for LWE samples was determined as 10.43% for the seventh sample which housed under cage free conditions and fed with organic (omega3+EPA+DHA) fortifiers, while it was found with a value 25.7% for the second and third LEY samples possessing a not fortified feeding parameters. The highest moisture content was determined as 78.37%, 54.64%, and 89.11 for thirty-first LWE sample (with not fortified feeding), third LEY sample (with not fortified feeding) and sixth LEW sample (having cage free and organic parameters), respectively. As a result, the minimum, average, and maximum contents of the chemical and physical quality parameters were determined for laying hen eggs raised in several housing and feeding conditions in Turkey.